BROADCASTING BETTER HEALTH: HEALTH PROMOTION AND COMMUNICATION STRATEGIES AT A NONPARTISAN INSTITUTION - DeWeese, Karsen (My University, 2025)
Background: Health promotion is an important skillset in the field of public health, and physical activity is a health behavior that provides an excellent example of why it is important. Health communication is a developing aspect of health promotion and education that requires specific knowledge and expertise. Health literacy ties into both health communication and health promotion due to the need for audiences to understand the messages professionals give, and health literacy rates are extremely low in the United States. Finding ways to be innovative, change messaging, and ensure audiences understand health promotional or educational material is imperative to the public health mission. Utilizing theories such as the Health Belief Model and the Social Cognitive Theory are great options to tackle this knowledge and perception challenge. Methods: The Applied Practice Experience was completed at the nonprofit, nonpartisan institution of the Kansas Health Institute during the Summer of 2024. Working with both project staff and the communication team, Karsen produced three distinct products discussed in this report. Results: The three products that were produced over the course of the Applied Practice Experience were two podcast episodes, quantitative data analytics combined with qualitative interview transcripts, and a resource guide for closed captioning and transcription processes for the Kansas Health Institute staff members. Discussion: This project paired with the previous coursework undertaken and extra experiences throughout the graduate student experience developed professional skills in the field of public health as well as communication. Limitations include the fact that some of the practices are not necessarily innovative, but the approach behind them is what is new to the field. Helping a nonpartisan institution such as the Kansas Health Institute produce high-quality products that educate the public pushes public health forward.
Keywords: Equitable; Health literacy; Nonprofit; Social cognitive theory; Health belief model; Health education